Chemical Composition and Biological Activities of Tunisian Ziziphus lotus Extracts: Evaluation of Drying Effect, Solvent Extraction, and Extracted Plant Parts - Touka Letaief; Stefania Garzoli; Valentina Laghezza Masci; Jamel Mejri; Manef Abderrabba; Antonio Tiezzi; Elisa Ovidi (Plants, 2021)
The Tunisian Ziziphus lotus plant was investigated to determine its phytoconstituents and evaluate its biological activities. In particular, the GC/MS technique was used to describe the chemical composition of Z. lotus active extracts and fractions. Among the obtained extracts, the yields of the dried root methanolic extract (29.80%) and the fruit aqueous extract (48.00%) were the highest ones. The dried root methanolic extract exhibited the highest amount in the total phenolics (186.44 ± 0.26 mg GAE/g DW), total flavonoids (102.50 ± 3.53 mg QE/g DW), and tannins (60.714 ± 2.2 mg catechin/g DW). The root aqueous extracts revealed the highest antioxidant activity with an IC50 of 8.96 ± 0.38 mg/L and 16.46 ± 0.60 mg/L for the ABTS•+ and DPPH• assays, respectively. The total antioxidant capacity was accorded to the methanolic extract of the dried roots with a value of 304.07 ± 1.11 µg AAE/mg. The drying process was found to improve the qualitative and quantitative properties of the Z. lotus extracts. The evaluation of the cytotoxic activity against the SH-SY5Y cell line was carried out using MTT assay. The petroleum ether and dichloromethane extracts of the dried roots showed relevant cytotoxic activities. The thin layer chromatography and the GC-MS/GC-FID analysis led to the identification of the 13-epimanool as a potent cytotoxic compound.